Pengenalan Keamanan Data Pribadi di Era Digital Bagi Masyarakat Desa Silo Lama - Sahren; Riki Andri Yusda; Cecep Maulana; Nurhaisyah (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: The development of digital technology in Indonesia has penetrated even rural areas, but it is not accompanied by an adequate understanding of personal data security. Rural communities tend to be vulnerable to cyber threats due to limited digital literacy. The purpose of this Community Service (PkM) activity is to increase awareness and knowledge of the community of Silo Lama Village, Silau Laut District, about the importance of personal data security in the digital era. The implementation method includes outreach, education, and practical training for the community using a participatory approach. The material presented includes the definition of personal data, types of cyber threats, how to protect personal information, and an introduction to the Personal Data Protection Law. The activity was attended by 30 participants consisting of village officials, community leaders, and the general public. The results of the activity showed a significant increase in participants' understanding of personal data security, from an average pre-test score of 45% to 82% in the post-test. Participants were also able to identify various forms of online fraud and implement data protection measures. This program has made a positive contribution to improving the digital literacy of rural communities and is expected to prevent losses due to cybercrime in the future. Keywords: cyber; data; digital; security; village Abstrak: Perkembangan teknologi digital di Indonesia telah merambah hingga ke wilayah pedesaan, namun tidak diimbangi dengan pemahaman yang memadai tentang keamanan data pribadi. Masyarakat desa cenderung rentan terhadap ancaman siber karena keterbatasan literasi digital. Tujuan dari kegiatan Pengabdian kepada Masyarakat (PkM) ini adalah untuk meningkatkan kesadaran dan pengetahuan masyarakat Desa Silo Lama, Kecamatan Silau Laut tentang pentingnya menjaga keamanan data privat. Metode kegiatan meliputi sosialisasi, edukasi, dan pelatihan praktis kepada masyarakat dengan pendekatan partisipatif. Materi yang disampaikan mencakup pengertian data pribadi, jenis-jenis ancaman siber, cara melindungi informasi pribadi, serta pengenalan UU Perlindungan Data Pribadi. Kegiatan dihadiri dengan 30 orang meliputi unsur pejabat desa, tokoh warga, dan warga umum. Hasil kegiatan memaparkan peningkatan pemahaman warga terkait keamanan data pribadi, dari rerata skor pre-test 45% menjadi 82% pada post-test. Peserta juga mampu mengidentifikasi berbagai bentuk penipuan online dan menerapkan langkah-langkah perlindungan data. Program ini memberikan kontribusi positif dalam upaya meningkatkan literasi digital masyarakat desa dan diharapkan dapat mencegah kerugian akibat kejahatan siber di masa mendatang Kata kunci: data; digital; desa; keamanan; siber